Knapp, Annelie, Erwin Otto, Gerd Stratmann, Merle Tönnies, eds. British Drama of the 1990s. Heidelberg: Universitäts verlag C. Winter, 2002. 201. pp. - Kurdi, Mária (FOCUS: Papers in English Literary and Cultural Studies, 2024)
This collection of essays was commissioned, according to the Introduction, by the editors of the series anglistik & englischunterrict (13), which suggests to the reader that the research findings in English Studies provided by the individual volumes are regarded as teaching aids at the same time. It is certainly a healthy way of combining and thus widening academic functions and practical purposes. The outcome, in the present case, is a volume abundant in information yet being considerably more than just a storehouse of names, titles and useful statistical data about the appearance of new authors and the welcome rise in the number of theatre-goers. A balance between ambitions is successfully achieved by including essays which offer a survey of trends and/or subcategories in the field under scrutiny to introduce other writings concerned with smaller parts of the whole.